Pengaruh Pembayaran Non Tunai Terhadap Jumlah Uang yang Diminta Masyarakat - Ayu Nursari; I Wayan Suparta; Yoke Moelgini (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2019)
Technological developments have touched aspects of life, including the economic sector of the banking sector. Along with advances in financial technology, commercial transactions continue to experience changes in the pattern and payment system (payment), which influences facilitate the reach of the public with bank financial products. Currently, the role of cash payments has begun to be shifted to technology advances. The purpose of this study was to determine the effect of non-cash fees (Debit / ATM Cards, Credit Cards, E-Money, Clearing, RTGS) on the economy and demand for cash in Indonesian society. This study uses Bank Indonesia (BI) and the Central Statistics Agency (BPS). The research data used is quarterly time data with 2013 sample time: 1 to 2018: 4. The data analysis technique used is the Error Correction Model (ECM) and Trend Analysis. The study results show that non-cash payments (Debit / ATM Cards, Credit Cards, E-Money, Clearing, RTGS) have a positive effect on the economy and demand for cash in Indonesian society.